Willingness to Pay for Kubah National Park : Evidence from the Contingent Valuation Method - Nor Afiza, Abu Bakar; Dayang Affizzah, Awang Marikan; Salbiah, Edman; Dayang Haszelinna, Abang Ali (Human Resource Management Academic Research Society, 2021)
The purpose of this study is to estimate Kuching residents’ (non-visitors) willingness to pay (WTP) for the conservation of Kubah National Park, Sarawak. In order to answer the research objectives in this study, Contingent Valuation Method (CVM) was put into application as the elicitation method and there were 160 respondents who involved in this data collection, where the random sampling method was executed. A dichotomous choice CVM (DC-CVM) was adopted and logit models were used to analyze the CVM analysis. The empirical results indicated that as the price increases, the probability in saying ‘Yes’ decreases. The minimum estimated mean for the WTP is an increment of 4.38% (RM0.44) while the maximum estimated mean is an increment of 200.24% (RM20.24). In addition, work status, education level attainment and income show positive and significant results.